Formal Analysis and Principal Architectural Character of Caunus Theater - Say Ozer, Yasemen; Ozer, Nevzat Oguz (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2017)
The ancient city of Caunus lies on the southwest shore of Anatolia, across the island of Rhodes. In the present time, it is located within the borders Koycegiz town and is on the western bank of the Dalyan River, which connects Lake Koycegiz with Mediterranean Sea. A port in earlier times, the city now is at quite a distance from the seashore due to the formation of the Dalyan Delta. Its harbor's location was strategically important for ships sailing between Aegean Sea and the Eastern Mediterranean. The Caunus Theater, situated towards southwest and overlooks the city and sea, is one of the best preserved among the Anatolian theaters as well as other structures of Caunus. Owing to the topography of the site, while the seats situated on the east of the theatre are located on a reformed rock, the seats on the north and west are supported by analemma. Analemma along with some of the seats and the stage are currently in ruins. However, during the process initiated by the founding of an archeological park in the city together with its immediate surroundings, a detailed architectural documentation of the city buildings has been planned. This documentation aims not only to document the buildings in isolation but also to indicate the location of the buildings within the city and the relations between the buildings and the topography. Digital coordinate measuring equipment are used for measuring the land, and the fundamental geometry of the theater are recorded in detail. All structural elements are measured meticulously, and a detailed 3-dimensional picture of the theater is created, from which a restituition model is generated in digital format. We have attempted to identify the principal characteristics of the structure using simulations performed on the digital model.
Keywords: Antique theater; Caunus; Greek theatre; Vitruvius; Architecture